(untitled) (Annals of Medical Research, 2021)
Aim: This study aimed at evaluating the PSG results of the applicants of driving license by reference to the BMI, and investigating the accuracy of this cutoff value of BMI (33) on detecting the patients with OSAS among the applicants of driving licenseMaterials and Methods: Driving license applicants with a BMI 36 constituted the group B. The AHI levels of the groups were compared, and ROC analyzes were performed to detect accurate BMI values. Results: Median AHI values did significantly differ among three groups (p0.001). median AHI was statistically significantly higher in group A (median AHI: 12.5) and in group B (median AHI: 12.9) compared to the control group (median AHI: 2.4) (p0.001). However, there was no significant difference between the median AHI of the group A and B (median AHI: 12.5 vs. 12.9) (p= 0.336). Additionally, 34 was found to be the cut-off value for BMI suggesting that AHI could be 15 and/or above; and 34.8 was found to be the cut-off value for BMI suggesting that AHI could be 30 and/or above. Conclusion: Patients with a BMI over 33 had a greater AHI compared to the patients. Additionally, 34.8 value was found to be the cut-off value for BMI suggesting that AHI could be 30 and/or above.